Vehicle and Pedestrian Safety Assessment at Unsignalized Intersection using Surrogate Safety Assessment Model: A Case Study of Old Sinamangal Intersection, Kathmandu, Nepal - Budhathoki, Sanjeev; Shrestha, Pradeep Kumar; Tiwari, Hemant (Journal on Transportation System and Engineering, 2025)
Intersections are one of the key elements of a road network to ensure the safety of the network because intersections have a lot of conflict points. The intersection at Old Sinamangal, Kathmandu is a three legged unsignalized intersection. During peak hours, it handles 3,759 vehicles and facilitates the movement of 318 pedestrians within the same timeframe. Microsimulation software VISSIM was used to model the intersection and Surrogate Safety Assessment model (SSAM) was used to identify location and type of conflicts. The intersection has 3341 number of conflicts in the peak hour among different vehicle types and pedestrians. The conflicts mainly occur where interchanges between vehicle and pedestrian takes place. Among 3341 conflicts at the peak hour, 1469 crossing conflicts, 1518 rear end conflicts and 339 lane change conflicts occur. The alternatives related to regulation of speeds were observed to be more effective in reducing vehicle-vehicle conflict but increased vehicle-pedestrian conflicts, and the alternatives related to grade separation between vehicles and pedestrians i.e. pedestrian bridge was more effective in reducing vehicle-pedestrian conflict. Furthermore, the alternative of shifting pedestrian crossing reduced both vehicle-vehicle and vehicle pedestrian conflicts.